A polymeric silver thiosaccarinate complex with a two-dimensional triply entangled mesh and argentophilic interactions - Dennehy, Mariana (2016)
Silver(I) complexes with sulfur-donor ligands have a broad range of pharmacological applications. One of the most important factors for tuning the biological activity is the type of donor atom and the ease of ligand replacement. Silver thiosaccharinates display a wide range of structures from mono- to polynuclear complexes. We report the synthesis, crystal structure and vibrational spectroscopic analysis of a two-dimensional AgI-thiosaccharinate coordination polymer, namely poly[tris([mu]2-4,4'-bipyridine-[kappa]2N:N')bis([mu]3-1,1-dioxo-1,2-benzisothiazole-3-thiolato-[kappa]3N:S3:S3)bis([mu]2-1,1-dioxo-1,2-benzisothiazole-3-thiolato-[kappa]2S3:S3)tetrasilver(I)], [Ag2(C7H4NO2S2)2(C10H8N2)1.5]n, with 4,4'-bipyridine acting as a spacer. A relevant feature of the structure is the presence of an unusually short Ag...Ag separation of 2.8859 (10) Å, well within the range of argentophilic interactions and confirmed as such by Raman analysis of the low-frequency spectrum. From a topological point of view, the structure presents interpenetration in the form of a threefold entangled 2D[rightwards arrow]2D mesh (2D is two-dimensional).